A history of Venice from its origins to the sixteenth century - SAPORI, A. (PSL Quarterly Review, 2014)
A review article of Gino Luzzatto’s Storia economica di Venezia dall’XI al XVI secolo, Venice, “Centro internazionale delle arti e del costume”, 1961. Apart from its vividness and fidelity in reconstructing the events which Venice has experienced during the course of several centuries, the fundamental importance of the volume lies in the questions it raises: reticular problems of a city and general problems of time, which are obviously interlinked. Here, the author confines himself to indicating some of those problems. JEL: N13, N43